Pengembangan Desa Jomboran sebagai Desa Agrowisata Mandiri Melalui Model Pembanguna Karakter, Model Tetrapreneur, dan Pemetaan Potensi Desa Berbasis Pertanian - Siwi Indarti; R. Edwin Indarto; Rika Fatimah PL; Miftahul Ajri (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
ABSTRACT Jomboran, one of the villages located in Klaten Tengah, Klaten, Central Java. Jomboran Village is an economical strategic area as it is close to the administrative center of Klaten. Jomboran Village with its potentials can be developed as a tourist village based on agriculture combined with the uniqueness of environmental conditions and cultural wealth of the community.The Jomboran village development method is carried out through three stages: identification of potential and mapping of areas, especially agricultural land; institutional programs and village financial institutions; and village tourism branding program.The programs that have been implemented are the improvement of community motivation through workshop with the theme "Building Powerful Character Towards Jomboran Tourist Village"; training the basics of business to potential community groups to improve the village economy; agricultural extension and technical guidance to farmer group members; Exhibition of the Creative Economy of Featured Products Jomboran, and the initiation of tropical fruit garden as an educational park.Through the UGM Guided Village Program, the potentials of Jomboran village can be synergized into attractive village tour package and have market opportunities.  Keywords: agrotourism; community quality; institutional; tetrapreneur; village.